Africa Agriculture Trade Monitor 2024 - Odjo, Sunday; Traoré, Fousseini; Zaki, Chahir (AKADEMIYA2063, 2024)
The 2024 AATM investigates critical issues related to African agricultural trade. As in previous editions of the report, we have developed a database that corrects discrepancies in trade flow values, as reported by importing and exporting countries, as the basis for analyzing Africa’s international, domestic, and regional economic community (REC) trade. Given the pressing need to address climate change and curb greenhouse gas emissions, this year’s AATM takes an in-depth look at the relationship between climate change, water use, and emissions and African agricultural trade.